1993
DOI: 10.1111/j.1945-5100.1993.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐profiles and surface enrichment of the halogens in four Antarctic H5 chondrites and in two non‐Antarctic chondrites

Abstract: Abstract-Depth-profiles of F, C1, Br and I concentrations were determined in four different Antarctic H5 chondrites from the Allan Hills and in the two chondrites Allende (C3) and Holbrook (L6). Pieces of the meteorites were studied by analysis of stepwise removed layers of 0.5-1.0 mm thickness up to a depth of 9 mm. Neutron activation analysis and ion-selective potentiometry were used for the determination of C1, Br, I and for F, respectively. The Antarctic meteorites show higher concentrations of the halogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
4
7
1
Order By: Relevance
“…Rock samples showed a decrease of the iodine -but not bromine and chlorine -concentration from the surface to the centre of the samples, leading to the conclusion that atmospheric iodine compounds react with surfaces of Antarctic rocks. This finding was confirmed by halogen depth profiles in Antarctic chondrides, which showed an enrichment in iodine at the surface not present in samples anywhere else in the world (Langenauer and Krähenbühl, 1993). Heumann et al (1987) found an iodine enrichment not only on meteorites, but also in Antarctic snow samples.…”
Section: Introductionsupporting
confidence: 68%
“…Rock samples showed a decrease of the iodine -but not bromine and chlorine -concentration from the surface to the centre of the samples, leading to the conclusion that atmospheric iodine compounds react with surfaces of Antarctic rocks. This finding was confirmed by halogen depth profiles in Antarctic chondrides, which showed an enrichment in iodine at the surface not present in samples anywhere else in the world (Langenauer and Krähenbühl, 1993). Heumann et al (1987) found an iodine enrichment not only on meteorites, but also in Antarctic snow samples.…”
Section: Introductionsupporting
confidence: 68%
“…In fact, no iodine content was obtained for JG-1, for which RNAA yielded a value with a large uncertainty due to poor counting statistics. For Allende, our RNAA and RPAA values for I are consistent with each other and also with literature data 2,5,14,15 except one value. 17 It is noted that some variation in I values may stem from the heterogeneous distribution of iodine in meteorite samples.…”
Section: Determination Of Halogens In Some Geological and Cosmochemicsupporting
confidence: 79%
“…As seen in Table 7, our RNAA data for Allende and geological reference rocks are reasonably consistent with literature values. [13][14][15][16] Although RPAA has nominally comparable sensitivity to that of RNAA as shown in Table 4, no data could be reliably obtained for geological standard rocks by RPAA, being consistent with detection limit values listed in Table 5. Iodine.…”
Section: Determination Of Halogens In Some Geological and Cosmochemicsupporting
confidence: 49%
See 2 more Smart Citations